The industrial organization of post-trade clearing and settlement - Milne, Alistair (Journal of Banking & Finance, 2007)
The introduction to this special issue reviews the literature on the industrial organization of securities market clearing and settlement, covering institutional, theoretical, and empirical contributions, including both papers in this special issue and previous studies. Clearing and settlement is an important but under-researched network industry. Recent theoretical research has characterized the network externalities in clearing and settlement and explored the economic efficiency of various alternative industrial structures. Initial empirical research has identified substantial economies of both scale and scope and important interactions with trading platforms. More research is needed to elaborate these theoretical insights and improve our understanding of the economics of this major industry.